Association of triglyceride glucose–body mass index and left ventricular hypertrophy in patients with IgA nephropathy: a retrospective study - Menglei Jv; Jun Zhang; Yuzhang Han; Anni Yang; Ye Zhu (European Journal of Medical Research)
Abstract Introduction IgA nephropathy (IgAN) is one of the most prevalent forms of glomerulonephritis worldwide, particularly affecting 40–50% of the East Asian population. Cardiovascular mortality represents a leading cause of death in patients with IgAN. Left ventricular hypertrophy (LVH) serves as a predictor of heart failure and cardiovascular mortality. Previous studies have indicated that Triglyceride glucose–body mass index (TyG–BMI), a surrogate marker for insulin resistance surrogates, correlated with the development of LVH. However, there is a lack of information available regarding the association between TyG–BMI and LVH in patients with IgAN. This study aims to explore the relationship between TyG–BMI and LVH in this population. Methods This retrospective study was conducted in the Fifth Affiliated Hospital of Sun Yat-sen University recruiting inpatients with renal biopsy-confirmed IgAN who were over the age of 18 years. Left ventricular dimensions were assessed through echocardiography. Linear regression and multivariate logistic regression analyses were performed using R language software and SPSS to investigate the association between TyG–BMI levels and LVH risk. Statistical significance was set at p < 0.05. Results A total of 327 patients with IgAN were enrolled in this study. Left ventricular mass index (LVMI) was positively correlated with TyG–BMI index (corr. coefficient: 0.453, p < 0.001) and inversely correlated with eGFR (corr. coefficient: -0.392, p < 0.001). After adjusting for age, gender, smoking, alcohol use, hemoglobin, low-density lipoprotein cholesterol, Scr, and urine output, advanced age and higher levels of hemoglobin and Scr were independently associated with increased TyG–BMI (p < 0.05). The odds ratios of the highest quartile of TyG–BMI compared with the lowest quartile were 8.39 (95%CI 1.66–42.39; p = 0.010). Conclusions Our findings indicated that the TyG–BMI level was positively correlated with LVMI. A high TyG–BMI level was independently associated with an increased risk of LVH in patients with IgAN. TyG–BMII demonstrated predictive ability for LVH in IgAN patients.